Superiority of AbCross enzyme-linked immunosorbent assay cross-match over the B-cell complement-dependent lymphocytotoxicity cross-match - Gombos, Petra; Opelz, Gerhard; Scherer, Sabine; Morath, Christian; Zeier, Martin; Schemmer, Peter; Langer, Robert; Süsal, Caner (Transplantation proceedings, 2013)
Background - The AbCross enzyme-linked immunosorbent assay (ELISA) cross-match is a recently introduced solid phase cross-match technique with several technical advantages over the currently available Antibody Monitoring System ELISA cross-match. - Methods - In the present study, we investigated the potential superiority of AbCross over the traditional complement-dependent lymphocytotoxicity (CDC) B-cell cross-match (BXM). Pretransplant sera of 271 kidney transplant recipients who were transplanted at our center between 1998 and 2010 were tested in ELISA screening for the presence of human leukocyte antigen (HLA) antibodies and in AbCross and CDC for antibody reactivity against solubilized donor HLA class I and II antigens and donor B cells, respectively. - Results - Patients positive for HLA class I or II antibodies on ELISA screening had a significantly poorer graft outcome 2 years after transplantation than recipients who were negative for HLA antibodies (21% vs 6% graft loss; P = .002). Corresponding with this finding, 37 recipients positive for HLA antibodies in AbCross against donor HLA class I or II antigens had a 2-year post-transplant graft loss rate of 19%, which is significantly higher than the 8% rate in 186 recipients who were negative for both antibody classes in AbCross (P = .043). The 2-year graft loss rate in 34 AbCross positive but BXM negative patients was 21%, compared with 7% in 172 AbCross and BXM negative patients (P = .012) and 9% in 11 AbCross negative but BXM positive patients (P = .39). - Conclusions - Our data indicate that the AbCross ELISA cross-match is superior to the CDC BXM, most likely because it detects antibodies against donor HLA antigens at a higher sensitivity.